Effects of inclined state and rolling motion on gas–liquid effective interfacial area in a rotating packed bed. (16th January 2023) - Chen, Wen-Cong; Chen, Xin-Tuo; Wang, Ze-Xin; Chu, Guang-Wen; Zhang, Liang-Liang; Chen, Jian-Feng
Graphical abstract: Highlights: The effective interfacial area in an RPB under offshore conditions were studied. The periodic fluctuation of the effective interfacial area with rolling was revealed. Increasing rotational speed was found to be effective against the liquid collection. Abstract: Confined space and floating environment present high challenges for gas–liquid separation and purification processes on offshore platforms. Rotating packed beds (RPBs) have shown great potential in onshore application, but its performance under offshore conditions remains unclear. This study first investigates the effective interfacial area ( a e ) within an RPB under inclined and rolling conditions by using the CO2 chemisorption method. The inclined state and rolling motion significantly affect a e, which is determined jointly by the secondary axial distribution and gas flow direction. The adverse effects occur at low rotational speed ( N ) due to the liquid collection driven by the gravity component, and increasing N was found to effectively against the collection and improve a e . Furthermore, a e under different motion periods and operating conditions were also investigated, and its relative rates of change and fluctuation can reach up to 17.4% and 10.7%, respectively. These results suggest that RPBs are somewhat resistant to marine conditions, providing the basis for offshore applications.